2011
DOI: 10.1007/s11207-011-9865-8
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Force-Free Extrapolation of Emerging Flux with a Global Twist and Serpentine Fine Structures

Abstract: We study the flux emergence process in NOAA active region 11024, between 29 June and 7 July 2009, by means of multi-wavelength observations and nonlinear force-free extrapolation. The main aim is to extend previous investigations by combining, as much as possible, high spatial resolution observations to test our present understanding of small-scale (undulatory) flux emergence, while putting these small-scale events in the context of the global evolution of the active region. The combination of these techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 49 publications
2
45
0
2
Order By: Relevance
“…At the beginning, only small portions of the original flux-rope emerge in the form of thin sea-serpent tubes (Strous et al, 1996;Pariat et al, 2004). Recently, Valori et al (2012) studied the emergence of an AR and found that the first manifestations of the emergence occur in the form of small bipoles, which are consistent with the sea-serpent scenario. The characteristic size of the bipoles can be associated with the instability wavelength (see also Bernasconi et al, 2002;Otsuji et al, 2011;Vargas Domínguez, van Driel-Gesztelyi, and Bellot Rubio, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…At the beginning, only small portions of the original flux-rope emerge in the form of thin sea-serpent tubes (Strous et al, 1996;Pariat et al, 2004). Recently, Valori et al (2012) studied the emergence of an AR and found that the first manifestations of the emergence occur in the form of small bipoles, which are consistent with the sea-serpent scenario. The characteristic size of the bipoles can be associated with the instability wavelength (see also Bernasconi et al, 2002;Otsuji et al, 2011;Vargas Domínguez, van Driel-Gesztelyi, and Bellot Rubio, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…A study by Valori et al (2012) brought together non-linear force-free field modelling and local correlation tracking of the photospheric flow patterns with high resolution coronal imaging and spectroscopic observations of the emergence of AR 11024. The flow patterns in this AR revealed converging motions of opposite magnetic polarities in the U-loop sections followed by flux cancellation, indicative of magnetic reconnection.…”
Section: Peculiality Of Flux Emergence Phase: Serpentine Flux Tubesmentioning
confidence: 99%
“…So far, these models have not been applied to real solar cases, but have been tested by the use of semianalytic force-free magnetic field solutions. Only Valori et al (2012b) investigated the helicity content of an AR during flux emergence and found a relative helicity of ≈10 42 Mx 2 prior to background, i.e., B-level flaring activity. The hesitation to apply the developed methods certainly arises from the strong influence the choice of a particular gauge as well as its numerical implementation may have on the model outcome, especially when applied to real data.…”
Section: Relation To Flare Productivitymentioning
confidence: 99%